SOCIAL NETWORKS AND POLITICS - G. R. Sufi yanova; E. O. Zudova (Сравнительная политика, 2018)
Book Review: Ceron, Andrea. Social Media and Political Accountability Bridging the Gap between Citizens and Politicians. London: Palgrave Macmillan, 2017. 236 p.